The effects of postpartum routine intrauterin treatments on fertility in cows - Yunus Çetin; Örsan Güngör; İbrahim Taşal; Cevat Sipahi; Sait Şendağ; Mehmet Yıldız; Axel Wehrend (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study was to determine the effect of treatment protocols on fertility in cows without the diagnosis of endometritis on postpartum period. Materials and Methods: The study consisted of 380 randomly selected cows with first lactation and milking for 17-30 days. In the study, there were 4 groups, 3 trials and 1 control group. Lugol Group (n=118) was treated with lugol iodide diluted with physiological saline, Peracetic Group (n=81) treated with acid solution diluted with physiological saline and Antibiotic Group (n=89) treated with a combination of oxytetracycline hydrochloride, trimethoprim and sulfadoxine. The Control Group (n=92) was not treated. Trial groups were scored 1-3 according to vaginal discharge and uterus score. Results: As a result of the study, the rates of total pregnancy for Group Lugol, Group Perasetic, Group Antibiotic and Group Control were 52,5%, 33,3%, 62,9%, 56,5%, respectively (p <0,01). The mean number of artificial inseminations per pregnancy ( number of artificial inseminations/number of pregnancy cows) was 5,3, 8,3, 4,1 and 4,1, respectively, and the mean open days count was 186,8, 215,6, 163,1, and 168,7, respectively (p <0,01). Conclusion: In the early postpartum period, the application of intrauterine antibiotics or antiseptics routinely to cows regardless of the endometritis situation does not contribute significantly to fertility. In addition, the use of high irritation chemicals in this period propably may cause damage to the healthy endometrial tissue, leading to a decrease in fertility rates.